Pengaruh Sosial Media Tiktok terhadap Nasib Kebudayaan Nasional - Ahmad Zulkifli (STAI DDI Kota Makassar, 2021)
This study aims to determine the effect of tiktok in cultural decline in Indonesia. Based on this research, it shows that the influence of tiktok on culture is very important, where tiktok has become the most widely used social media in the daily life of some circles. National culture is also experiencing a decline due to the trend that appears in Tiktok, many of which feature foreign cultures. The awareness of some circles is also lacking to study culture is another reason why cultural values ​​are starting to decline. Qualitative descriptive analysis is a method of assessment used with the aim of uncovering facts, circumstances, and phenomena. The variables in this study are the globalization of media and Indonesian arts and culture. By using a qualitative descriptive analysis, this study reveals the impact of the development of technological globalization on Indonesian cultural arts.